(New page: <math>X(\omega ) = \delta(\omega ) + \delta(\omega - 5) + \delta(\omega - 5)\,</math>)
 
Line 1: Line 1:
 
<math>X(\omega ) = \delta(\omega ) + \delta(\omega - 5) + \delta(\omega - 5)\,</math>
 
<math>X(\omega ) = \delta(\omega ) + \delta(\omega - 5) + \delta(\omega - 5)\,</math>
 +
 +
<math>x(t) = \int_{-\infty}^{\infty}X(\omega )e^{j\omega t}d\omega\,</math>

Revision as of 13:19, 7 October 2008

$ X(\omega ) = \delta(\omega ) + \delta(\omega - 5) + \delta(\omega - 5)\, $

$ x(t) = \int_{-\infty}^{\infty}X(\omega )e^{j\omega t}d\omega\, $

Alumni Liaison

has a message for current ECE438 students.

Sean Hu, ECE PhD 2009